Minimizing tissue damage due to filler injection with systemic hyperbaric oxygen therapy - Hong, Woo Taik (Arch Craniofac Surg, 2019)
Recently, there is a growing interest of hyperbaric oxygen therapy in many fields of medicine. We had a 43-year-old female patient presented with severe necrosis of the nose, philtrum, and upper lip due to retrograde arterial occlusion after nasolabial fold hyaluronic acid filler injection. Our patient went through 43 sessions of systemic hyperbaric oxygen therapy from December 2, 2017 to January 18, 2018. We administered 2.8 atmosphere absolute (ATA) for 135 minutes in the first session and the remaining sessions consisted of 2.0 ATA for 110 minutes. In reporting this case, we wish to provide a warning regarding the latent risk of filler injections and share our experience about minimizing soft tissue damage in the early stages with systemic hyperbaric oxygen therapy.